CGRP-induced migraine-like headache in persistent post-traumatic headache attributed to mild traumatic brain injury - Håkan Ashina; Afrim Iljazi; Haidar M. Al-Khazali; Thien Phu Do; Anna K. Eigenbrodt; Eigil L. Larsen; Amalie M. Andersen; Kevin J. Hansen; Karoline B. Bräuner; Basit Ali Chaudhry; Casper E. Christensen; Faisal Mohammad Amin; et al. (The Journal of Headache and Pain, 2022)
Abstract Objective To ascertain whether intravenous infusion of calcitonin gene-related peptide (CGRP) can induce migraine-like headache in people with persistent post-traumatic headache attributed to mild traumatic brain injury (TBI) and no pre-existing migraine. Methods A non-randomized, single-arm, open-label study at a single site in Denmark. Eligible participants were aged 18 to 65 years and had a known history of persistent post-traumatic headache attributed to mild TBI for ≥ 12 months. All participants received continuous intravenous infusion of CGRP (1.5 µg/min) over 20 min. A headache diary was used to collect outcome data until 12 h after the start of CGRP infusion. The primary end point was the incidence of migraine-like headache during 12-hour observational period. Results A total of 60 participants completed the study protocol and provided data for the analysis of the primary end point. The median age was 32.5 (IQR, 25.5–43.0) years; 43 participants (72%) were female. Following CGRP infusion, 43 (72%) of 60 participants developed migraine-like headache during the 12-hour observational period. The median time to peak headache intensity was 40 min (IQR, 20–60), and the median peak headache intensity was 6 (IQR, 5–8) on the 11-point numeric rating scale. Conclusion Intravenous infusion of CGRP is a potent inducer of migraine-like headache in people with persistent post-traumatic headache attributed to mild TBI. This observation underscores the importance of CGRP in the genesis of migraine-like headache that is often experienced by individuals who are afflicted by persistent post-traumatic headache. Further research is warranted to ascertain whether other signaling molecules also contribute to the disease mechanisms underlying post-traumatic headache.